Predicting runoff series in ungauged basins of the Brazilian Cerrado biome. (March 2022) - Althoff, Daniel; Rodrigues, Lineu Neiva; Silva, Demetrius David da
Abstract: Information concerning water availability in a basin can be key to trustworthy and robust decisions, and reduce disputes over water among its multiple users. The Cerrado region, however, lacks basic hydrological information concerning water availability in many of its basins. In this study, two regionalization frameworks based on the donation of parameter sets from a hydrological model calibrated in gauged catchments were assessed. These approaches were evaluated using a leave-one-out cross-validation for the gauged catchments. Parameters donation by spatial proximity led to KGE and rNSE of 0.58 and 0.56, while by attributes proximity led to KGE and rNSE of 0.56 and 0.45, respectively. A regional-sample data set for the Cerrado (HydroCerrado) was made available with information compiled for the 411 gauged catchments used in this study and runoff time series simulated for 4531 level 5 ottobasins by donating parameter sets by spatial proximity. Highlights: A regional-sample data set is made available with catchments from the Cerrado biome. Regionalization of a hydrological model is assessed by spatial or physical proximity. Streamflow series are obtained for 4531 hydrologic units in the Cerrado biome.